Phylogenetic diversity of actinomycetes cultured from coastal multipond solar saltern in Tuticorin, India - Jose, Polpass Arul (BioMed Central, 2012)
BACKGROUND: Hypersaline solar salterns are extreme environments in many tropical and subtropical regions throughout the world. In India, there are several coastal solar salterns along with the coastal line of the Bay of Bengal and Arabian Sea and inland solar salterns around Sambhar saltlake, from which sodium chloride is obtained for human consumption and industrial needs. Studies on characterization of such coastal and inland solar salterns are scarce and both the bacterial and archaeal diversity of these extreme saline environment remains poorly understood. Moreover, there are no reports on exclusive diversity of actinomycetes inhabiting Indian solar salterns. RESULTS: Soil sediments were collected from both concentrator and crystallizer ponds of solar salterns and subjected to detailed physico-chemical analysis. Actinomycetes were selectively isolated by employing selective processing methods and agar media. A total of 12 representatives were selected from the 69 actinomycete isolates obtained from the saltern soil samples, using Amplified Ribosomal DNA Restriction Analysis. Sequencing and analysis of 16S rDNA from chosen representative isolates displayed the presence of members affiliated to actinobacterial genera: Streptomyces, Micromonospora, Nocardia, Nocardiopsis, Saccharopolyspora and Nonomuraea. The genus Streptomyces was found to be the dominant among the isolates. Furthermore, rare actinomycete genus Nonomuraea was isolated for the first time from Indian solar salterns. CONCLUSIONS: To the best of our knowledge, this study constitutes the first characterization of actinomycete diversity centred on solar salterns located in the eastern coastal region of India. Furthermore, this is the very first report of isolation of Nonomuraea species from solar salterns and also from India. As actinomycetes encompass recurrently foremost sources of biotechnologically important member of the microbial communities, the actinomycetes retrieved from the Indian saltern soil samples laid the platform to search for novel biotechnologically significant bioactive substances.